Tanggung Jawab Pengusaha dan Bentuk Perlindungan Hukum Terhadap Pekerja yang Dipekerjakan Melebihi Jam Kerja Lembur - Sunaryo, Hanavia Rahma; Pattipawae, Dezonda Rosiana; Kuahaty, Sarah Selfina (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
Employers have employed workers in excess of the overtime work hours determined by law with the aim of reaping greater profits while the rights of workers during overtime are set aside. purposes of the research analyze and discuss the responsibility of employers or employers for excess overtime hours imposed and to find out the forms of legal protection for workers employed in excess of the overtime hours prescribed by law. Methods of the research this type of research uses normative juridical methods, with qualitative processing and analysis of legal materials. Results of the research that approving an employment relationship above a deviation in overtime working hours based on laws and regulations is considered to have negated one of the elements of the employment agreement. The employer must be responsible for providing the rights of workers and bear everything that arises as a result of the actions taken. Then, to protect workers from deviations and violations of rights, legal protection is carried out through education and socialization of labor law instruments to workers and employers / employers as well as through the authority of supervisory institutions that will act to prevent and overcome labor violations.